Tinjauan Hukum atas Implementasi Undang-Undang No. 17 Tahun 2023 tentang Kesehatan terhadap Operasional Rumah Sakit Swasta Tercatat di Bursa Efek Indonesia - Rifki Rifki (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2026)
Law Number 17 of 2023 concerning Health (the 2023 Health Law) serves as a fundamental regulation governing various aspects of health services in Indonesia, including the operations of private hospitals. For private hospitals whose shares are listed on the Indonesia Stock Exchange (IDX), the implementation of the 2023 Health Law has brought significant changes in both legal and operational dimensions. This study aims to examine the legal aspects of implementing the 2023 Health Law on the operations of IDX-listed private hospitals. Employing a normative legal research method with statutory and conceptual approaches, this study analyzes relevant regulations and doctrines. The results indicate that the 2023 Health Law expands the scope of hospitals' legal liability, comprehensively regulates the obligations and rights of both hospitals and patients, and imposes stricter sanctions for violations. Furthermore, the implementation of this regulation impacts the business and financial aspects of listed private hospitals, including expansion opportunities, shifts in cost structures, and stock market responses. However, challenges remain in its application, such as diverse interpretations of certain provisions and hospitals' readiness to comply with the established requirements.